2020
DOI: 10.2196/13851
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Course Evaluation Methods: Systematic Review

Abstract: Background Massive open online courses (MOOCs) have the potential to make a broader educational impact because many learners undertake these courses. Despite their reach, there is a lack of knowledge about which methods are used for evaluating these courses. Objective The aim of this review was to identify current MOOC evaluation methods to inform future study designs. Methods We systematically searched the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 46 publications
(204 reference statements)
0
35
0
3
Order By: Relevance
“…The studies in the current synthesis derive from Alturkistani et al’s systematic review of MOOC evaluation methods [ 21 ]. Their review included studies from 2008 to 2018 that focused primarily on MOOC evaluation and studies that reviewed or applied MOOC evaluation methods.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies in the current synthesis derive from Alturkistani et al’s systematic review of MOOC evaluation methods [ 21 ]. Their review included studies from 2008 to 2018 that focused primarily on MOOC evaluation and studies that reviewed or applied MOOC evaluation methods.…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with the epistemological stance of this review. The complete search strategy and further details of the source review [ 21 ] can be found in [ 18 ]. Alturkistani et al [ 21 ] identified 3275 records; after a review procedure, the final review included 33 studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations